How to Bring the Ocean into the Concert Hall: Beethoven’s Third Symphony and the Aesthetics of the Sublime - Næsted, Henrik (Danish Yearbook of Musicology, 2004)
In the period around the genesis of Beethoven’s Eroica Symphony, the sublime was an immensely important aesthetic category. Through Schiller’s adaptation of it into the sphere of arts, Kant’s treatment of the subject (in Kritik der Urteilskraft, 1790) in particular reverberated in musical debates. Thus, around the turn of the century we find a number of essays in leading music periodicals (e.g. Allgemeine musikalische Zeitung) which attempt to define the musical sublime. Departing from the fact that numerous linguistic tropes from this discussion surface in the reception of the Eroica, this article presents a musical analysis which has as its main claim that this particular work falls within the paradigm of the sublime. In continuation of this analysis, it is discussed which general conclusions on the possibility of the musical sublime may be derived from this concrete appearance. This leads to the conclusion that the musical sublime only makes sense in an interplay with musical beauty.